LUT-based aerosol size distribution from wavelet de-noised 355-nm and 532-nm Mie lidar signals - Bagtasa, Mannelyn Dela Cruz (Animo Repository, 2005)
Eleven Aerosol Size Distributions (ASD) (from Ur- ban to Maritime with 9 logarithmic increments in between them) was simulated in this study to generate a Lookup Table (LUT). In the simulations, aero- sol size ranged from 0.001-10μm with 1.40 to 1.60 real and 0.000-0.030 imaginary refractive indices for the 355-nm and 532-nm LIDAR wavelengths. The extinction coefficients (σ) were calculated using Fernald’s inversion method on the LIDAR data de- noised using the Haar wavelet. The ASD in the De La Salle University area was determined by comparing (σ532/σ355)EXPT to (σ532/σ355)THEO values found in the LUT. The ASD of the data analyzed falls on the two extreme ASD models considered. Results have also shown that the ASD, and consequently the type of aerosols interacting with the LIDAR, is affected by the local meteorological conditions and man’s activities (e.g., fireworks during New Year’s eve).